Occupational Health Challenges among Hotel Housekeepers - Iing, Iing; Mariawati, Ade Sri; Duana, I Made Kerta (Universitas Airlangga, 2025)
Introduction: Hotel housekeepers face several occupational health hazards, including physical, emotional, and environmental stressors. These workers usually face various obstacles, such as physical strain, emotional stress, low income, etc. However, there has been minimal examination of these difficulties. This review aimed to investigate the occupational health challenges faced by hotel housekeepers. Method: A systematic review was carried out during August and September 2024, using databases such as Google Scholar, PubMed, and ScienceDirect. The search focused on research published between 2014 and 2024, including keywords such as